Faktor yang Berhubungan dengan Terjadinya Unmet Need KB pada Pasangan Usia Subur (PUS) di Kota Yogyakarta - Susiana Sariyati; Sundari Mulyaningsih; Sri Sugiharti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2015)
The problem of population is important big issues and urgent, primarily related with aspects of the quality of population control, improving the quality of population and mobility of population, if its associated with the potential threat of explosion of population. The purpose of this study was to know factors associated with unmet need family planning among reproductive age couples in Yogyakarta. This study used descriptive method. The populations of this study were all of reproductive age couples in Yogyakarta. The sampling technique was done by probability proportional to size resulted on 779 respondents of reproductive age couples from 30 sub village in 30 village in Yogyakarta. The results of study showed that there was no significant relationship between respondent ages and unmet need, no significant relationship between wife education and unmet need, and no significant relationship between the number of children still live and unmet need.